Dynamic anticipation by Cdk2/Cyclin A-bound p27 mediates signal integration in cell cycle regulation - Maksym Tsytlonok (Nature Portfolio, 2019)
The cyclin-dependent kinase (Cdk) inhibitor p27Kip1 (p27) folds upon binding to Cdk/cyclin complexes and during cell cycle progression p27 becomes phosphorylated, which triggers its ubiquitination and degradation. Here the authors use an integrated approach and show that Cdk2/cyclin A-bound p27 samples lowly-populated conformations that dynamically anticipate the sequential steps of the signaling cascade.